O tecer perceptivo dos alunos do ensino fundamental acerca do seu cotidiano - Feitosa, Josenilde Santos (2024)
The current research focuses on the analysis of the perception of students in the final years of elementary school at the Colégio Estadual Jornalista Paulo Costa, located in the Assis Chateaubriand neighborhood (Bugio), in the northern part of Aracaju/SE, with eighth-grade students, considering the meaning they attribute to their living environment (school and living environment) in light of the concepts of topophilia and topophobia by the Chinese-American geographer Yi-Fu Tuan, anchored in the theoretical assumptions of phenomenology defended by Merleau- Ponty. Therefore, our research question is: can the relationships that subjects weave with their living environment be revealed in a topophilic, topophobic relationship or another way of reading and perceiving everyday life? This is a study focused on qualitative research because it deals with an analysis of the experiences of subjects in relation to their lived world. The instrumental itinerary is based on bibliographical research that encompasses all stages of the research, with reference to the theoretical basis involving reading and analysis of the environment, perception, topophilia, topophobia, signs and meanings, environment-subject-nature relationship, mental maps, among others; field research based on semi-structured observation, with pre-established scripts, collection of informal reports concomitant with the observations, application of the mental map technique based on the Kozel methodology. In view of the above, we conclude that the research in question is relevant due to the possibility of contributing to studies involving the society-nature relationship, since we are increasingly forced to distance ourselves from our environment in order to see ourselves in a separate and objectified way. Regarding the product, a booklet was created whose focus lies in valuing the subjects as an integral part of their environments that bring together their life stories. The booklet can be used by teachers in Basic and Higher Education as a pedagogical instrument that includes a booklet of knowledge, stories, and the perspective of subjects in their daily lives.